2016
DOI: 10.1002/pon.4242
|View full text |Cite
|
Sign up to set email alerts
|

Real-world implementation of electronic patient-reported outcomes in outpatient pediatric cancer care

Abstract: When implementing ePROs in outpatient pediatric oncology practice, HCPs report determinants that influence ePRO integration. To improve implementation and outcomes, tailored organizational (eg, formal ratification by management and time) and specific local (eg, individualized assessments) strategies should be developed to achieve optimal ePRO discussion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
131
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 74 publications
(145 citation statements)
references
References 47 publications
7
131
0
3
Order By: Relevance
“…The barriers for PRO assessment found in our sample were mainly based on practical issues in the organization (i.e., time, insufficient staff, and logistics). These are comparable to those reported in PRO studies performed in adult samples and in one pediatric oncology sample . Of concern, we found that HCPs from developing countries indicate routine assessment of PROs to be useful, but do not seem to have the resources (i.e., financial, logistics, and availability of staff) to be able to integrate such assessments in their clinical care.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The barriers for PRO assessment found in our sample were mainly based on practical issues in the organization (i.e., time, insufficient staff, and logistics). These are comparable to those reported in PRO studies performed in adult samples and in one pediatric oncology sample . Of concern, we found that HCPs from developing countries indicate routine assessment of PROs to be useful, but do not seem to have the resources (i.e., financial, logistics, and availability of staff) to be able to integrate such assessments in their clinical care.…”
Section: Discussionsupporting
confidence: 80%
“…Furthermore, as medical HCPs indicate PRO information to be useful, there can be a difference between intentions and actual behavioral change (e.g., when the user lacks control over the behavior, or when psychosocial support is not always readily available) . Practical issues could be addressed and barriers ameliorated with sufficient staffing and training of staff and by providing ways to integrate PRO monitoring in clinical routines (e.g., investing in efficient technology systems that can integrate PRO data into the electronic file, and appointing a coordinator/facilitator for the implementation process) . The PROMIS with its validated items banks and innovative electronic PRO systems could provide an efficient way to collect PRO data in pediatric practice.…”
Section: Discussionmentioning
confidence: 99%
“…As part of a larger study, families of patients with newly diagnosed cancer were asked to participate in this study in four pediatric oncology centers in the Netherlands: the Amalia Children's Hospital/ Radboud University Medical Center Nijmegen, the Emma Children's Hospital/AMC Amsterdam, the Sophia Children's Hospital/Erasmus MC Rotterdam, and the VU University Medical Center Amsterdam. During a 19‐month period between June 2012 and December 2013, newly diagnosed patients were identified.…”
Section: Methodsmentioning
confidence: 99%
“…Potential users need to be convinced of the additional value of innovations for their patients and their own practice before implementation . Information about possible additional value of PAT next to clinical judgment, is therefore mandatory.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation